(untitled) (Journal of Civil Engineering Researchers, 2025)
Concrete-filled double-shell circular steel columns consist of two concentric steel tubes with the space between them filled with concrete. These columns are a suitable option for high-rise construction due to their lower weight and also allow the passage of cables and utilities. In this research, modelling was carried out in Abaqus software and parametric analysis was performed based on variables such as the shape and dimensions of the stiffeners. The results show that concrete-filled double-shell columns perform better against axial and seismic loads than columns without concrete. The total and square stiffeners give the best performance, but it is not possible to increase their number due to space constraints. Trapezoidal stiffeners are also effective in improving axial and lateral performance, but result in a reduction in ductility. Circular stiffeners have the greatest reduction in ductility and their use is limited. In general, the choice of stiffener type has a significant effect on the performance of double shell columns.